Associations among serum VEGF and CGRP levels with the peripheral vascular blood flow of the skin of the hands in women with Fibromyalgia. (February 2023) - Casas-Barragán, Antonio; García-Ríos, María Carmen; Rus, Alma; Tapia-Haro, Rosa María; Correa-Rodríguez, María; Aguilar-Ferrándiz, María Encarnación
Abstract: Background: Fibromyalgia (FM) is a long-term condition of unknown physiopathology, whose hallmark symptoms are diffuse musculoskeletal chronic pain and fatigue. Objectives: We aimed to analyze the associations among serum vascular endothelial growth factor (VEGF) and calcitonin gene-related peptide (CGRP) levels with the peripheral temperature of the skin of both hands and the core body temperature in patients with FM and healthy controls. Methods: We conducted a case-control observational study with fifty-three women diagnosed with FM and twenty-four healthy women. VEGF and CGRP levels were spectrophotometrically analyzed in serum by enzyme-linked immunosorbent assay. We used an infrared thermography camera to assess the peripheral temperature of the skin of the dorsal thumb, index, middle, ring, and pinkie fingertips and dorsal centre as well as the palm thumb, index, middle, ring, and pinkie fingertips, palm centre and thenar and hypothenar eminences of both hands and an infrared thermographic scanner to record the tympanic membrane and axillary temperature. Results: Linear regression analysis adjusting for age, menopause status, and body mass index showed that serum VEGF levels were positively associated with the maximum ( β = 65.942, 95% CI [4.100, 127.784], p = 0.037), minimum ( β = 59.216, 95% CI [1.455, 116.976], p = 0.045), and mean ( β = 66.923, 95% CI [3.142, 130.705], p = 0.040) temperature of the thenar eminence of the non-dominant hand, as well as with the maximum temperature of the hypothenar eminence of the non-dominant hand ( β = 63.607, 95% CI [3.468, 123.747], p = 0.039) in women diagnosed with FM. Conclusions: Mild associations were observed between serum VEGF levels and the peripheral temperature of the skin in hand areas in patients with FM; therefore, it is not possible to establish a clear relationship between this vasoactive molecule and vasodilation of the hands in these patients. Highlights: VEGF is related to peripheral temperature of hand skin at thenar and hypothenar sites in Fibromyalgia. VEGF could be related to dysregulation of hands temperature in patients with Fibromyalgia. CGRP may not be associated with hand peripheral temperatures or central temperature in Fibromyalgia.